2022
DOI: 10.1111/bcp.15446
|View full text |Cite
|
Sign up to set email alerts
|

Apelin is expressed throughout the human kidney, is elevated in chronic kidney disease & associates independently with decline in kidney function

Abstract: Aims Chronic kidney disease (CKD) is common and cardiovascular disease (CVD) is its commonest complication. The apelin system is a potential therapeutic target for CVD but data relating to apelin in CKD are limited. We examined expression of the apelin system in human kidney, and investigated apelin and Elabela/Toddler (ELA), the endogenous ligands for the apelin receptor, in patients with CKD. Methods Using autoradiography, immunohistochemistry and enzyme‐linked immunosorbent assay, we assessed expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
(99 reference statements)
1
5
0
Order By: Relevance
“…This is the first time, to our knowledge, that a fluorescent ligand has been used in this way to explore endogenous apelin receptor in human tissue. The pattern of distribution closely matched previous findings in an immunohistological study assessing apelin expression in the human kidney ( 60 ). One limitation of using 488 nm wavelength fluorophores in tissue section imaging is that there can be considerable interference by autofluorescence of natural proteins such as elastin.…”
Section: Discussionsupporting
confidence: 87%
“…This is the first time, to our knowledge, that a fluorescent ligand has been used in this way to explore endogenous apelin receptor in human tissue. The pattern of distribution closely matched previous findings in an immunohistological study assessing apelin expression in the human kidney ( 60 ). One limitation of using 488 nm wavelength fluorophores in tissue section imaging is that there can be considerable interference by autofluorescence of natural proteins such as elastin.…”
Section: Discussionsupporting
confidence: 87%
“…Apelin receptor mRNAs are found extensively across various tissues, including the brain, lungs, heart, spinal cord, kidneys, adipose tissue, and skeletal muscle [13-15]. In the human kidney, the APJ/apelin system is expressed throughout the renal unit, predominantly in the cortex and vasculature[16, 17]. Activation of the apelin system in the kidney can improve renal blood flow, diuresis, and reduce inflammation and fibrosis[18].…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences in apelin levels remain elusive. One study in healthy volunteers and patients with chronic kidney disease (CKD) found 60% higher plasma apelin concentrations in women than in men [ 15 ], and another study showed that female patients with osteoarthritis had higher apelin levels than men [ 31 ]. In contrast, we did not find a sex difference in SIAD patients, and Blanchard and colleagues also found comparable apelin levels in healthy men and women of more than 60 years of age (age group of our cohort).…”
Section: Discussionmentioning
confidence: 99%
“…AVP and apelin are secreted from neurosecretory cells of the hypothalamic supraoptic and paraventricular nuclei and apelin receptors [ 12 ] and arginine vasopressin receptors (AVPR)1a/1b are expressed by magnocellular AVP neurons [ 13 ]. In the kidneys, apelin receptors are found in the glomeruli and in all nephron segments including the collecting duct where AVPR2 are also expressed [ 14 , 15 ]. In states of water depletion and hyperosmolality, AVP is released by the posterior pituitary.…”
mentioning
confidence: 99%